Battery charge controller for photovoltaic (PV) system / Mohd Azhar Zamri - Zamri, Mohd Azhar (2009)
This thesis presents a report on the development of battery charge controller for stand alone Photovoltaic (PV) system. Battery charge controller is a most importance part in stand-alone photovoltaic (PV) systems and it is the components that require completing the system. In general, a standalone PV system consists of a PV array, which converts sunlight to direct-current electricity, energy storage in the form of secondary batteries, loads or appliances, and a control system, which battery charge controller charging and operation of the load. This paper presents typical strategies for battery charge regulation or controller and load control used in stand alone PV systems. The project was developing to introduce 5 stages of development which are literature review, conceptual design, physical design, program or unit testing, and experimental test and hardware modification. Experimental tests have shown satisfactory results during the testing process at the Power Electronic Laboratory and Photovoltaic Monitoring Center (PVMC). The result shows the battery voltage increase during the charging using Pulse Width Modulation (PWM) method and the controller able to monitor battery temperature increases.